2005
DOI: 10.1021/ma0484882
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Telomerization Kinetics of N-Isopropylacrylamide Using 3-Mercaptopropionic Hydrazide as Chain Transfer Agent

Abstract: The telomerization (chain transfer polymerization) kinetics of N-isopropylacrylamide were investigated in various (hydro)organic solvents using 3-mercaptopropionic hydrazide as chain transfer agent (telogen). Except for the dioxane/water system telogen consumption rates were similar for all cases, while solvent effects could be observed for the monomer consumption rates. Chain transfer constants, as defined by the ratio of the rate constants for chain transfer and chain propagation (C T = k tr,/k p), were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…With the aim of obtaining more information we analysed the efficiency of 2‐mercaptoethanol as chain transfer agent in the polymerization of NDMAm. Thiols have long been employed as efficient, nearly ideal, chain transfer agents in the polymerization of acrylamide and N ‐isopropylacrylamide monomers 23, 42, 43. We found that the addition of millimolar concentrations of the thiol to the NDMAm polymerization reduces markedly the molecular weight of the polymer, with a negligible decrease of the polymerization rate.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…With the aim of obtaining more information we analysed the efficiency of 2‐mercaptoethanol as chain transfer agent in the polymerization of NDMAm. Thiols have long been employed as efficient, nearly ideal, chain transfer agents in the polymerization of acrylamide and N ‐isopropylacrylamide monomers 23, 42, 43. We found that the addition of millimolar concentrations of the thiol to the NDMAm polymerization reduces markedly the molecular weight of the polymer, with a negligible decrease of the polymerization rate.…”
Section: Resultsmentioning
confidence: 85%
“…As described for free radical polymerization of acrylamide‐derived monomers, R P for NDMAm photoinitiated by azo compounds at low conversion can be expressed by the classical free radical kinetic law, given by22–24 where I a is the intensity of the light absorbed by the photoinitiator, Φ i is the initiation quantum yield, [M] is the molar monomer concentration and k p and k t are the propagation and termination rate constants, respectively. This implies that degradative chain transfer and primary radical termination processes can be considered as negligible.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of thermal initiation ( R i ,th ) can be estimated from the slope of a first‐order plot (Fig. 11) according to eq 10: Based on a slope of 3.19 × 10 −6 and a literature value for k p / k t 0.5 = 0.24 M 0.5 s 0.5 in DMF at 65 C,50 one obtains R i ,th = 1.8 × 10 −10 s −1 . Assuming that R i ,th is independent of conversion, the concentration of chains generated by spontaneous initiation is equal to R i ,th multiplied by the polymerization time (longest time = 36 h), which gives 2.3 × 10 −5 M. Considering that the MI concentration is 6.7 × 10 −3 M or higher, it can be safely concluded that the contribution of spontaneous initiation to the overall number of chains in the system is insignificant (especially considering that the value of k p / k t 0.5 will be higher at 120 °C than at 65 °C).…”
Section: Resultsmentioning
confidence: 99%
“…The progress of reactions and the purity of products were monitored by TLC on Silufol UV-254 plates using benzene-acetone (4 : 1; IIIa-IIIm) or ethyl acetatepyridine-water (12 : 5 : 4; Va-Ve) as eluent. 3-Sulfanylpropionic acid hydrazide (II) was synthesized according to the procedure described in [16].…”
Section: Methodsmentioning
confidence: 99%